Writing up your action research project - McNiff, Jean (Routledge, 2016)
Many practice-based researchers have expert knowledge of doing research but often experience difficulties when writing it up and communicating the significance of what they have done. This book aims to help bridge the gap. Packed with practical advice and strong theoretical resources it takes you through the basics of designing and producing your text so that it will meet established standards and high quality assurance expectations.